(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Urogenital infections affect millions of people every year worldwide. The management of these diseases usually requires the use of antimicrobial agents. And more newly, the use of probiotic Lactic acid bacteria [LAB] cultures in the management of vaginal infections and other infections has been extensively studied. In this work 30 isolates of Lactobacillus spp. Were obtained from healthful Iraqwomen,s vagina. All the isolates were subjected to the cultural microscopically and biochemical examinations for the identification of species add to the identification by Vitek2 system [ANC card]. The results showed that half of isolates belongs to Lactobacillus casei and the other half belongs to Lactobacillus gasseri. agar well diffusion method and disc method are used to detect of bacteriocin production byLactobacillus.casei isolates against 4 species of Gram positive and Gram negative pathogenic bacteria which included:Corynebacteriumurealyticum, Staphylococcus aureus , Escherichia coli and Psudomonasaeuroginosa, which obtained from IMAMEIN KADHIMEN MEDICAL CITY . The results showed the Lactobacillus which isolated from vagina by well diffusion method was effective against pathogenic isolates more than the Lactobacillus isolated by blank disc method , the high inhibitory effect of Lactobacillus isolates by well give an inhibition zone reached to [26] mm , while the Lactobacillus by disc was lower with inhibition reached to [18]mm. The supernatant did not show any activity when was treated with NaOH and adjusted to pH 7. This indicates that the organic acid produced by the Lactobacillusisolates was may be actually responsible for the inhibition of the indicator bacteria .The result show that the Lactobacillusstrains could be considered as potential antimicrobial probiotic strains against some human vaginal pathogens and should be further studied for their human health benefits .